Activated Thiol Sepharose‐based proteomic approach to quantify reversible protein oxidation. Issue 11 (26th August 2019) - Xu, Yang; Andrade, Joshua; Ueberheide, Beatrix; Neel, Benjamin G.
Abstract : Reactive oxygen species (ROS) can act as second messengers in various signaling pathways, and abnormal oxidation contributes to multiple diseases, including cancer. Detecting and quantifying protein oxidation is crucial for a detailed understanding of reduction‐oxidation reaction (redox) signaling. We developed an Activated Thiol Sepharose‐based proteomic (ATSP) approach to quantify reversible protein oxidation. ATSP can enrich H2 O2 ‐sensitive thiol peptides, which are more likely to contain reactive cysteines involved in redox signaling. We applied our approach to analyze hereditary leiomyomatosis and renal cell carcinoma (HLRCC), a type of kidney cancer that harbors fumarate hydratase (FH)‐inactivating mutations and has elevated ROS levels. Multiple proteins were oxidized in FH‐deficient cells, including many metabolic proteins such as the pyruvate kinase M2 isoform (PKM2). Treatment of HLRCC cells with dimethyl fumarate or PKM2 activators altered PKM2 oxidation levels. Finally, we found that ATSP could detect Src homology region 2 domain‐containing phosphatase‐2 and PKM2 oxidation in cells stimulated with platelet‐derived growth factor. This newly developed redox proteomics workflow can detect reversible oxidation of reactive cysteines and can be employed to analyze multiple physiologic and pathologic conditions.—Xu, Y., Andrade, J., Ueberheide, B., Neel, B. G. Activated Thiol Sepharose‐based proteomic approach to quantify reversible protein oxidation. FASEB J. 33, 12336–12347 (2019). www.fasebj.org